Photochemistry of single optically trapped oleic acid droplets. (January 2021) - Parmentier, Evelyne A.; David, Grégory; Arroyo, Pablo Corral; Bibawi, Simone; Esat, Kıvanç; Signorell, Ruth
Abstract: We report the photodegradation of optically trapped oleic acid droplets by visible light in the absence of additional reactive gaseous species. The temporal evolution of the droplet's chemical composition and size is monitored by Raman spectroscopy and elastic light scattering, respectively. The dependencies on the oxygen amount in the surrounding gas phase ( 0–20%), the droplet size ( 500–3000 nm in radius), and the laser power and wavelength are investigated. The oxygen amount and the droplet size have only a very minor influence on the reaction rate, if at all. By contrast, the reaction becomes substantially faster at higher laser power and shorter wavelength. The experimental observations indicate that mechanisms involving the photoexcitation of oleic acid are the dominant pathways. Our study reveals that direct photodegradation has to be accounted for when using optical traps or applying spectroscopic and light scattering characterization methods to study aerosol particles that contain fatty acids. Highlights: Oleic acid droplets photodegrade even in the absence of reactive gaseous species. Photo-degradation is dominated by mechanisms involving photoexcited oleic acid. This is important for optical trapping and spectroscopic characterization.